I saw this formula while studying Fourier Transform:(adsbygoogle = window.adsbygoogle || []).push({});

[Sum of δ(t-lT) from l=-infinity to l= +infinity] = 1/T * [Sum Of exp(jlΩt) from l=-infinity to l=+infinity].

I am having trouble getting this into my head. How do I prove it or understand the physical meaning of this formula?

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Representing sum of delta functions as sum of exponentials

**Physics Forums | Science Articles, Homework Help, Discussion**